Daylighting metrics: An approach to dynamic cubic illuminance - Monteoliva, Juan Manuel (2018)
Advances in research work in the field of numerical analysis of daylight performance have generated in-depth knowledge on photometric measurements of daylight quality. Most dynamic metrics are based on illuminance, which is a two-dimensional concept insofar as it is concerned with the density of luminous flux incident at a point on a surface. In order to extend dynamic metrics into the third dimension and consider the distribution of illumination at a point in space, it is important to generate new advances in simulation environments and consider spatial illumination metrics. In this context, the main objective of the present work was to advance in the development of cubic dynamic daylight metrics, as a complement to the two dimensional analysis currently employed, promoting the use of Climate Based Daylight Modelling (CBDM). For this purpose, cylindrical to horizontal illuminance ratio is applied to dynamic simulation paradigm developing the concept of useful modeling indexs (UMIs). The research methodology applied in this work is divided into two main parts: (i) two dimensional concept: spatial daylight autonomy (sDA(300lx,50%)-horizontal-, sDA(175lx,50%)-vertical-) and uniformity, and (ii) three dimensional concept: useful cylindrical to horizontal illuminance ratio (uEcl/Eh(0.3-0.6)). In order to assess this method, two spaces (RR1 and RR2) of the Lavalle Public Library, located in Mendoza-Argentina, were taken as a case study. Results show important differences in horizontal illuminance between RR1 and RR2 (∆sDA(300lx, 50%) > 80%). Similar values of uEcl/Ewp(0.3-0.6)-useful cylindrical to horizontal illuminance ratio-are detected in both rooms (RR1= 69.32 % and RR2= 72.24 %) in nodes near north opening. Yet there are significant differences (< 36%) of uEcl/Ewp(0.3-0.6) between nodes located near the south wall, this is due to the obstruction of a south opening in RR2. Furthermore, it is important to mention that 2D metrics display a more uniform behavior than 3D metrics. This shows itself clearly if we take into account that difference in sDA are much lower than difference in uEcl/Eh(0.3-0.6), if we compare nodes closest to the north windows to does that are far from it, in both rooms (RR1 and RR2). This results from the fact that cubic metrics are more sensitive to the direction of light. This is of crucial importance for daylight studies in clear sky condition, due to the defined direction of direct solar radiation. Finally, a new approach to daylighting performance analysis based on the addition of cubic metrics to dynamic daylight paradigm is proposed: useful modelling indexs (UMIs). UMIs make it possible to quantify annual occurrence of proper light modelling conditions. As an initial approach, cylindrical to horizontal illuminance ratio (Ecl/Ewp(0.3-0.6)) has been considered, due to its current use in international standards.